Physico-Chemical Studies on Praseodymium Soaps in Solid State - Shukla, R.K.; Mishra, Vikas (Asian Journal of Chemistry, 2016)
The physico-chemical characteristics of praseodymium soaps (butyrate and caprylate) in solid state were investigated by IR, X-ray diffraction and thermal measurements. The IR results reveal that the fatty acids exist in dimeric state through hydrogen bonding and soaps possess partial ionic character. The X-ray diffraction measurements were used to calculate the long spacings and the results confirm the double layer structure of praseodymium soaps. The decomposition reaction was found kinetically of zero order with energy of activation 8.154 and 7.697 kcal mol–1 for butyrate and caprylate, respectively.